Geographies of Energy—A Course in Sociotechnical Decision Making. (2nd September 2021) - Marshall, Lisa
Abstract: Energy plays an increasingly vital role in society where questions around technologies, economics, quality of life, and policies are debated. The link of nuclear energy with the social sciences allows for a fuller examination of human-environment decision making. This paper comes out of the Organisation for Economic Co-operation and Development (OECD) Nuclear Energy Agency (NEA) International Workshop on the Nuclear Social Science Nexus. The development and teaching of a Geographies of Energy course is provided as an example of a pedagogical method to understand the interconnectedness of science and social science. Students in the North Carolina State University China Study Abroad Program in Engineering, Science, Technology & Society (STS) and International Relations unpack the sociotechnical dimensions of resource extraction, energy production, consumption, and byproduct management. A complex network of resources, actors, implications, and outcomes arise, allowing for the study of place uniqueness as well as the connections and interactions between places—China, neighboring states, and international systems—and power technologies.